2023
DOI: 10.2147/ijn.s403882
|View full text |Cite
|
Sign up to set email alerts
|

The Current Progress of Tetrahedral DNA Nanostructure for Antibacterial Application and Bone Tissue Regeneration

Abstract: Recently, programmable assembly technologies have enabled the application of DNA in the creation of new nanomaterials with unprecedented functionality. One of the most common DNA nanostructures is the tetrahedral DNA nanostructure (TDN), which has attracted great interest worldwide due to its high stability, simple assembly procedure, high predictability, perfect programmability, and excellent biocompatibility. The unique spatial structure of TDN allows it to penetrate cell membranes in abundance and regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“… 33 Tetrahedral DNA nanostructures (TDNs) are a method of DNA nanotechnology that possess structural stability and rigidity, and are able to enter cells autonomously, in size-independent fashions. 34 TDNs are able to minimize electrostatic repulsion in the membrane and enter the cell without the assistance of transfection agents. Some studies have suggested that TDNs enter cells via a caveolin-dependent endocytosis pathway.…”
Section: Cellular Delivery and Uptake Of Pnamentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Tetrahedral DNA nanostructures (TDNs) are a method of DNA nanotechnology that possess structural stability and rigidity, and are able to enter cells autonomously, in size-independent fashions. 34 TDNs are able to minimize electrostatic repulsion in the membrane and enter the cell without the assistance of transfection agents. Some studies have suggested that TDNs enter cells via a caveolin-dependent endocytosis pathway.…”
Section: Cellular Delivery and Uptake Of Pnamentioning
confidence: 99%
“…Some studies have suggested that TDNs enter cells via a caveolin-dependent endocytosis pathway. 34 Recently, Zhang et al. developed an antisense PNA that was incorporated into a TDN, which was effectively taken up by cells.…”
Section: Cellular Delivery and Uptake Of Pnamentioning
confidence: 99%
“…Notably, the common symmetry principles guide the external and internal determinants of cell morphology, assembly, and functions of intracellular molecules. Understanding this fundamental commonality is necessary for neuroscience-inspired AI [212][213][214]. Protein assemblies adopting tetrahedral symmetry create shell-like architectures [215].…”
Section: Molecular-cellular Co-evolutionmentioning
confidence: 99%
“…Increased cell migration, osteogenic differentiation capacity, anti-inflammatory and ROS-scavenging capacity, and chondrocyte phenotypic maintenance capacity are some of these characteristics. These characteristics make TDN appropriate for application in bone tissue regeneration and repair as a tailored nanocarrier for medical treatments or as a bioactive nanomaterial . Jungju Oh et al studied the treatment of ischemic stroke and created a self-assembling nanoparticle made of deoxycholate-conjugated polyethylenimine-2k (DP2k), HO-1 plasmid, and hypoxia-specific antireceptor for advanced glycation end-product (RAGE) peptides.…”
Section: Pathophysiology Of Strokementioning
confidence: 99%
“…These characteristics make TDN appropriate for application in bone tissue regeneration and repair as a tailored nanocarrier for medical treatments or as a bioactive nanomaterial. 99 Jungju Oh et al studied the treatment of ischemic stroke and created a self-assembling nanoparticle made of deoxycholate-conjugated polyethylenimine-2k (DP2k), HO-1 plasmid, and hypoxia-specific antireceptor for advanced glycation end-product (RAGE) peptides. RAGE overexpression and inflammation are both present in the ischemic brain.…”
Section: In Vitro Andmentioning
confidence: 99%